Methods in Community-Based Participatory Research for Health - Israel, Barbara A, Eugenia Eng, Amy J. Schulz, Edith A. Parker (Jossey Bass, 2005)
Written by distinguished experts in the field, this book shows how researchers, practitioners, and community partners can work together to establish and maintain equitable partnerships using a Community-Based Participatory Research (CBPR) approach to increase knowledge and improve health and well-being of the communities involved. CBPR is a collaborative approach to research that draws on the full range of research designs, including case study, etiologic, longitudinal, experimental, and nonexperimental designs. CBPR data collection and analysis methods involve both quantitative and qualitative approaches. What distinguishes CBPR from other approaches to research is the active engagement of all partners in the process. This book provides a comprehensive and thorough presentation of CBPR study designs, specific data collection and analysis methods, and innovative partnership structures and process methods. This book informs students, practitioners, researchers, and community members about methods and applications needed to conduct CBPR in the widest range of research areas—including social determinants of health, health disparities, health promotion, community interventions, disease management, health services, and environmental health.